Proteomic analyses identify ARH3 as a serine mono-ADP-ribosylhydrolase - Jeannette Abplanalp (Nature Portfolio, 2017)
Protein ADP-ribosylation has emerged as a key post translational modification that regulates several stress responses. Here the authors characterize ARH3 as a major serine-specific mono–ADP-ribosylhydrolase and use a proteomics approach to identify the cellular targets of ARH3.